Postoperative pain scores and opioid consumption in opioid-dependent patients with cancer after intraoperative remifentanil analgesia: A prospective case-controlled study - Motamed, MD, Cyrus; Audibert, MD, Juliette; Albi-Feldzer, MD, Aline; Bouroche, MD, Gaelle; Jayr, MD, PhD, Christian (Journal of Opioid Management, 2017)
Background: Opioid dependency is becoming increasingly common among surgical patients with cancer, and can lead to inadequate pain relief during the initial postoperative period. No guidelines are currently available for the management of perioperative and postoperative morphine administration in these patients. As a first approach, the authors assessed the opioid requirements of these patients during the early postoperative period. Methods: A group of 35 consecutive surgical patients with cancer on opioid therapy (opioid-dependent group) for cancer pain were compared to a matched group of 44 surgical opioid-naive patients (control group). All patients underwent major head and neck or abdominal surgery. The following parameters were recorded and compared: preoperative and postoperative morphine consumption, patient-controlled analgesia records and Visual Analog Scale scores, intraoperative remifentanil and desflurane consumption, Bispectral Index monitoring values, heart rate, and blood pressure. Results: Remifentanil requirements were significantly higher (1.4-fold) in the opioid-dependent group compared to the control group (p < 0.05). On postoperative day 1, morphine requirements were significantly higher in the opioid-dependent group (2.3-fold) compared to the control group (p < 0.05). Baseline heart rate was significantly higher in the opioid-dependent group and this difference remained significant during surgery, no significant difference in blood pressure was observed between the two groups. Conclusion: This study shows a 40 percent increase of intraoperative remifentanil requirements in opioid-dependent patients during cancer surgery. Morphine requirements during the postoperative period were increased by up to 140 percent.